First Evidence of Cotinine in Canine Semen Reveals Tobacco Smoke Exposure - Debora Groppetti; Giulia Pizzi; Elisa Giussani; Alessandro Pecile; Silvia Michela Mazzola; Valerio Bronzo; Eleonora Fusi (Veterinary Sciences)
Tobacco smoke has numerous adverse effects on both human and animal health, including impaired reproductive function. Recent research has explored environmental exposure in dogs, investigating various biological matrices. However, no data are currently available on the presence of cotinine, a nicotine metabolite, in the canine ejaculate. This study aimed to evaluate the detectability of cotinine in the semen of dogs living with smoking owners. Additionally, seminal cotinine concentrations were correlated with those in serum and hair. To further examine the potential impact of smoking on canine fertility, the relationships between seminal cotinine, total sperm concentration, and antioxidant activity in plasma and semen were analyzed in exposed and non-exposed dogs. This study is the first to demonstrate the presence of cotinine in canine ejaculate and its correlation with blood and hair concentrations. While the potential toxic effect of cotinine on seminal parameters and male fertility in dogs requires further investigation, it is crucial to raise awareness among pet owners about the risks associated with domestic smoking for their animals.